Weed chemical control in the winter wheat planting after non fallow predecessors in the Northern Steppe of Ukraine - Tkalich, Yuriy; Ткаліч, Юрій; Тsyliuryk, Olexandr; Цилюрик, Олександр; Kozechko, Volodymyr; Козечко, Володимир; Rudakov, Yuriy; Рудаков, Юрій; Tkalich, Olga; Ткаліч, Ольга; Bagorka, Maria; Багорка, Марія (Faculty of Agriculture, University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2020)
The use of alfalfa as predecessors for winter wheat leads to the increase of weed infestation of its cultivation in the result of frequent cutting out of the culture during three years of use. It was shown that of winter wheat yields have had a higher level of weed infestation after non fallow predecessors with inadequate coverage of soil surface. Therefore they demand high-priority protection from weed sprouts. None of the studied herbicides was able to provide reliable protection of wheat crops from bromes (Bromus tectorum L.), as well as a sticky weed (Galium aparine L.). The tank mix of herbicides (Esteron – 0.8 l/ha + Puma Super – 0.8 l/ha) provides a reliable protection for winter wheat crops from many types of short-lasting weeds including the cattail grass (Setaria pumila L.), water grass (Echinochloa crusgalli L.). A significant suppressive effect on cereal weeds Super was registered for the herbicide Ellay. Використання люцерни як попередників для озимої пшениці призводить до збільшення зараження бур’янами її вирощування в результаті частого вирізання культури протягом трьох років використання. Показано, що врожаї озимої пшениці мали вищий рівень зараженості бур’янами після неперелогових попередників з недостатнім покриттям поверхні ґрунту. Тому вони вимагають пріоритетного захисту від паростків бур’янів. Жоден із досліджуваних гербіцидів не зміг забезпечити надійний захист посівів пшениці від бромів (Bromus tectorum L.), а також липкого бур’яну (Galium aparine L.). Резервуарна суміш гербіцидів (Естерон - 0,8 л / га + Puma Super - 0,8 л / га) забезпечує надійний захист посівів озимої пшениці від багатьох видів короткотривалих бур’янів, включаючи траву рогозу (Setaria pumila L.), водяну траву (Echinochloa crusgalli L.). Значний пригнічувальний ефект на злакові бур'яни Супер був зареєстрований для гербіциду Ellay.
Хімічний контроль бур’янів при посадці озимої пшениці після неперелогових попередників у Північному Степу України
Keywords: winter wheat; озима пшениця; weeds; бур’яни; herbicides; гербіциди; grain yield; урожай зерна